Does the CATCH Early Childhood Program Increase Physical Activity Among Low-Income Preschoolers?—Results From a Pilot Study. Issue 2 (February 2018) - Chuang, Ru-Jye; Sharma, Shreela V.; Perry, Cheryl; Diamond, Pamela
Purpose: To explore whether the physical activity (PA) component of the Coordinated Approach to Child Health Early Childhood (CATCH EC) program helps increasing preschoolers' PA during active times at preschool. Design: Nonrandomized controlled experimental study. Setting: Head Start centers in Houston, Texas, 2009 to 2010 school year. Participants: A total of 439 preschoolers aged 3 to 5 years (3 intervention centers, n = 220; 3 comparison centers, n = 219). Intervention: The CATCH EC preschool-based teacher-led nutrition and PA program. Measures: Preschoolers' PA was measured at baseline and postintervention using the System for Observing Fitness Instruction Time–Preschool version, a direct observation method measuring PA at the classroom level. Parent surveys provided demographic data. Analysis: Pre-to-post changes in preschoolers' PA were examined using the Mann-Whitney U test. Results: Results show a significant decrease in the percentage time preschoolers spent in level 2 PA (low activity) at intervention ( P = .005) and comparison ( P = .041) centers. Indoor vigorous activity increased significantly on an average by +6.04% pre-to-post intervention among preschoolers in the intervention group ( P = .049); no significant change was found in the comparison group. Conclusion: The CATCH EC favorably increased indoor vigorous PA level among low-income children attending Head Start.